Caffeic acid O-methyltransferase from Ligusticum chuanxiong alleviates drought stress, and improves lignin and melatonin biosynthesis - Huang, Enxia; Tang, Jie; Song, Simin; Yan, Han; Yu, Xinyi; Luo, Chenlu; Chen, Yineng; Ji, Huiyue; Chen, Anqi; Zhou, Jiayu; Liao, Hai (Frontiers in Plant Science, 2024)
Drought stress is a major constraint on plant growth and agricultural productivity. Caffeic acid O-methyltransferase (COMT), an enzyme involved in the methylation of various substrates, plays a pivotal role in plant responses to abiotic stress. The involvement of COMTs in drought response, particularly through the enhancement of lignin and melatonin biosynthesis, remains poorly understood. In this study, LcCOMT was firstly proposed to be associated with the biosynthesis of both lignin and melatonin, as demonstrated through sequence comparison, phylogenetic analysis, and conserved motif identification. In vitro enzymatic assays revealed that LcCOMT effectively methylates N-acetylserotonin to melatonin, albeit with a higher Km value compared to caffeic acid. Site-directed mutagenesis of residues Phe171 and Asp269 resulted in a significant reduction in catalytic activity for caffeic acid, with minimal impact on N-acetylserotonin, underscoring the specificity of these residues in substrate binding and catalysis. Under drought conditions, LcCOMT expression was significantly upregulated. Overexpression of LcCOMT gene in Arabidopsis plants conferred enhanced drought tolerance, characterized by elevated lignin and melatonin levels, increased chlorophyll and carotenoid content, heightened activities of antioxidant enzymes peroxidase (POD), catalase (CAT), and superoxide dismutase (SOD), and reduced malondialdehyde (MDA) and hydrogen peroxide (H2O2) accumulation. This study is among the few to demonstrate that COMT-mediated drought tolerance is achieved through the simultaneous promotion of lignin and melatonin biosynthesis. LcCOMT represents the first functionally characterized COMT in Apiaceae family, and it holds potential as a target for genetic enhancement of drought tolerance in future crop improvement strategies.